Spatio-temporal variation in peer effects - The case of rooftop photovoltaic systems in Germany - Johannes Rode; Sven Müller (European Regional Science Association (ERSA), 2016)
We study spatio-temporal variation of peer effects in rooftop photovoltaics adoption of households. Our investigation employs locational data on potential adopters and a geocoded data set of all grid-connected photovoltaic systems set up in Germany through 2010. The detailed locational data allows us to construct an individual measure of peer effects for each potential adopter across Germany. Based on a discrete choice model with panel data, our analysis reveals that peer effects are mostly localized within a range of 0-0.2 km. Within this range they deflate slowly in a non-linear manner. We also find that the peer effect decreases over time.
Keywords: O33; C35; Q55; R10; 330; Peer effects; installed base; discrete choice models; technology adoption; imitation; photovoltaics; solar; Germany